(untitled) (International Journal of Islamic Business, 2025)
In recent years, the growing emphasis on Environmental, Social, and Governance (ESG) has prompted the need of firms to integrate the sustainable development goals (SDG) with the ethical framework, particularly the religious aspect in their business operations. The objective of this study is to explore how Maqasid al-Shariah’s divine ethical framework complements and diverges from the secular models of SDG and ESG in promoting human welfare, sustainability, and moral governance. The qualitative desktop research methodology is employed to systematically assess the previous academic literature, laws and regulations, Islamic publications and latest ESG frameworks. This study reveals that Islamic finance principles, that are rooted in the Al-Quran, Al-Hadith and Maqasid al-Shariah, have been proven to significantly align with the fundamental values of ESG by fostering the environment protection (khalifah), social justice (adl) and finally, fair and equitable governance (amanah). However, due to the inconsistencies of metrics for both, few gaps are identified in integrating ESG into the Islamic finance framework. This study contributes to the literature by discussing the conceptual framework that integrate ESG, SDG and Maqasid al-Shariah principles in finance context. From the policymakers’ perspective, the findings may assist them in understanding the ESG policies and how they aligned with the Islamic values.